Smooth versus Textured Tissue Expanders: Comparison of Outcomes and Complications in 536 Implants - Allam, Omar; Dinis, Jacob; Almeida, Mariana N.; Junn, Alexandra; Mozaffari, Mohammad Ali; Shah, Rema; Chong, Lauren; Olawoyin, Olamide; Mehta, Sumarth; Park, Kitae Eric; Avraham, Tomer; Alperovich, Michael (Archives of Plastic Surgery, 2024)
Background Increasing concerns regarding the safety of textured surface implants have resulted in surgeons transitioning from textured tissue expanders (TEs) to smooth TEs. Given this change has only recently occurred, this study evaluated outcomes between smooth and textured TEs.Methods Women who underwent two-stage breast reconstruction using TEs from 2013 to 2022 were included. TE-specific variables, perioperative information, pain scores, and complications were collected. Chi-squared, t-test, and linear regression analyses were performed.Results A total of 320 patients received a total of 384 textured and 152 smooth TEs. Note that 216 patients received bilateral reconstruction. TEs were removed in 9 cases. No significant differences existed between groups regarding comorbidities. Smooth TEs had a higher proportion of prepectoral placement (p < 0.001). Smooth TEs had less fills (3 ± 1 vs. 4 ± 2, p < 0.001), shorter expansion periods (60 ± 44 vs. 90 ± 77 days, p < 0.001), smaller expander fill volumes (390 ± 168 vs. 478 ± 177 mL, p < 0.001), and shorter time to exchange (80 ± 43 vs. 104 ± 39 days, p < 0.001). Complication rates between textured and smooth TEs were comparable. Smooth TE had a greater proportion of TE replacements (p = 0.030). On regression analysis, pain scores were more closely associated with age (p = 0.018) and TE texture (p = 0.046). Additional procedures at time of TE exchange (p < 0.001) and textured TE (p = 0.017) led to longer operative times.Conclusion As many surgeons have transitioned away from textured implants, our study shows that smooth TEs have similar outcomes to the textured alternatives.
Keywords: breast reconstruction; tissue expanders; complications